The Halo surrounding native English speaker teachers in Indonesia - Kramadibrata, Angga (Indonesian Journal of Applied Linguistics, 2016)
The Native Speaker Fallacy, a commonly held belief that Native English Speaker Teachers (NESTs) are inherently better than Non-NESTs, has long been questioned by ELT researchers. However, this belief still stands strong in the general public. This research looks to understand how much a teacher’s nativeness affects a student’s attitude towards them, as well as the underlying reasons for their attitudes. Sixty seven respondents in two groups were asked to watch an animated teaching video, after which they completed a questionnaire that used Likert-scales to assess comprehensibility, clarity of explanation, engagement, and preference. The videos for both groups were identical apart from the narrator; one spoke in British English, while the other, Indian English. In addition, they were also visually identified as Caucasian and Asian, respectively. The video was controlled for speed of delivery. The quantitative data were then triangulated using qualitative data collected through open questions in the questionnaire as well as from a semi-structured interview conducted with 10 respondents. The data show that there is a significant implicit preference for NEST teachers in the video, as well as in respondent’s actual classes. However, when asked explicitly, respondents didn’t rank nativeness as a very important quality in English teachers. This discrepancy between implicit and explicit attitudes might be due to a subconscious cognitive bias, namely the Halo Effect, in which humans tend to make unjustified presumptions about a person based on known but irrelevant information.